An Overview of Cadmium, Chromium, and Lead Content in Bivalves Consumed by the Community of Santa Rosa Island (Ecuador) and Its Health Risk Assessment - Romero-Estévez, David; Yánez-Jácome, Gabriela S.; Dazzini Langdon, Mónica; Simbaña-Farinango, Karina; Rebolledo Monsalve, Eduardo; Durán Cobo, Gabriel; Navarrete, Hugo (Frontiers in Environmental Science, 2020)
Santa Rosa Island community members derive their income and livelihoods from bio-aquatic resources, principally bivalves of the genus Anadara, both for subsistence use and commercial purposes. Bivalve mollusks have a sedentary lifestyle and feed by filtering water, meaning they absorb all surrounding substances, including harmful elements like toxic metals. This study aimed to analyze different-sized samples of Anadara tuberculosa and Anadara similis, sediment, and Rhizophora mangle leaves to determine their total amount of cadmium, lead, and chromium as a first approach to the evaluation of the health risk related to the consumption of bivalves. For both species from four sampling sites, the results revealed metal concentrations in the bivalves between 0.211 and 0.948 mg·kg-1, 0.038 and 0.730 mg·kg-1, and 0.067 and 0.923 mg·kg-1 for Cd, Cr, and Pb, respectively. The calculated potential risk (>1) for cadmium, considering all body weights, showed a high health risk for consumers. In the case of lead, the results showed a high health risk in children. There was no risk found for chromium. For sediments, the mean values were 2.14, 29.99, and 12.37 mg·kg-1 and for the Rhizophora mangle leaves were 2.23, 4.22, and 3.35 mg·kg-1 for Cd, Cr, and Pb, respectively. These results did not show a relation with the metal content in bivalves.